Magnetostratigraphy: A Summary - Herman Darman; Edy Sunardi (Berita Sedimentologi, 1998)
Magnetostratigraphy is the element of stratigraphy that deals with the magnetic characteristics of rock units, obtained by measuring the direction and intensity of magnetism in rocks of different ages. The magnetic characteristic most often used, however, is the polarity of magnetic remanence. The polarity is said to be "normal" (north-seeking magnetization gives a northern hemisphere pole, as today) or "reverse" (north-seeking magnetization gives a southern hemisphere pole). The polarity is established from isolating of the primary remanent magnetism of the sample, using paleomagnetic investigation.Magnetostratigraphy defines the sequence of geomagnetic polarity reversals recorded during deposition of a geological formation. This approach can be a very valuable technique for the subsurface correlation of marine and continental sequences and is the only correlation technique which is independent of any facies control. It provides an important complement to biostratigraphy for core correlating and dating. In general the rock magnetic stratigraphy involves the utilization of magnetic properties of sediments and sedimentary rocks as a means of (1) stratigraphic correlation, (2) identification of sediment sources and transport mechanism, (3) characterization/detection of paleoenvironmental change.